Symbolic significance and cognitive dimension of the Latvian landscape - Ņitavska, Natalija (Landscape Architecture and Art, 2023)
As well as physical reality, the landscape is also an emotionally symbolic structure that closely intertwines with human cognitive perception, self-identification, with the perception of the homeland, as well as affects our daily habits. The landscape, as a cultural expression, forms a close connection with historical and political events, with traditions and customs, with each individual and with the nation as a whole, all of this manifests itself in a symbolic sense of the landscape, often used as a national recognition, for marketing purposes, but the symbols of the landscape are also a close connection between each individual and their native place and ancestors. The research analyses various aspects and phenomena that influence the symbolic importance of the landscape and relate to both cognitive aspects of each individual or community, nation, and collective memory and other expressions of identity and self-awareness. The landscape has a holistic nature that explains the close connection of several processes, both physical changes in landscape and changes in perception of each individual, according to the political and social situation of the country. Not least importance has the history of the development of the landscape perception of each country, which has been formed relatively recently in Latvia and art, photograms and the systematic division of the landscape created by researchers also play a big role in it. The regional context and cultural and historical division of Latvia should also be noted in the creation of landscape symbols. Cognitive processes are therefore associated with such concepts – Genius Locci, memory and event landscapes, landscape identity, place names, landscape biographies, etc. As a result, the author’s model for the development and operation of the symbolic meaning of the landscape is presented, reflecting the structure and specificity of the symbolic creation of the landscape, as well as related processes that influence the symbolic meaning of the landscape.